KEBENARAN DALAM PERSPEKTIF FILSAFAT ILMU DAN PENDIDIKAN AGAMA ISLAM - Syahlarriyadi (LPPM STAI Nida El-Adabi, 2022)
In general, when looking at the problems faced by humans, especially in facing the existence of life and efforts to achieve prosperity in this world and in the hereafter, the truth becomes an urgent thing to do. Even though in essence the truth that humans do is basically not absolute but relative in nature because indeed the human mind will not be able to obtain absolute truth, in this case the essential and absolute truth belongs only to Allah. The truth can be obtained in detail and depth based on research processes and scientific logical reasoning. The truth of science can be accepted as long as there are no facts that deny its truth. In uncovering the problem of Truth in the perspective of Islamic Philosophy and Education, qualitative research was carried out. The research was carried out using library research which is a theoretical study, references and other scientific literature related to the culture, values ​​and norms that develop in the social situation under study.